2018
DOI: 10.1002/pbc.27242
|View full text |Cite
|
Sign up to set email alerts
|

Using the MEDiPORT humanoid robot to reduce procedural pain and distress in children with cancer: A pilot randomized controlled trial

Abstract: The MEDiPORT study appears feasible to implement as an adequately-powered effectiveness-assessing trial following modifications to the intervention and study protocol. ClinicalTrials.gov NCT02611739.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 41 publications
3
91
0
8
Order By: Relevance
“…In another study by Jibb et al. (2018) , the NAO robot was used to reduce the pain and stress experienced by children with cancer during Subcutaneous Port (SCP) needle insertions, a specific medical procedure.…”
Section: Robots and Childrenmentioning
confidence: 99%
“…In another study by Jibb et al. (2018) , the NAO robot was used to reduce the pain and stress experienced by children with cancer during Subcutaneous Port (SCP) needle insertions, a specific medical procedure.…”
Section: Robots and Childrenmentioning
confidence: 99%
“…Dur tgt − Dur trn Dur orig − Dur trn (6) where Dur tgt is the singing target duration and Dur orig is the original duration of the retrieved vowel. When the vowel is stretched, Dur trn accounts for the duration of the unscaled transition (shadowed areas in Fig.…”
Section: Transformation Requirementsmentioning
confidence: 99%
“…The audios generated for one of the five scores have been provided as Additional files 1, 2, 3, 4, 5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23, and 24. Forty-nine Spanish native speakers took part in the test.…”
Section: Subjective Evaluation 431 Mushra Test Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent study of 57 children has demonstrated the effectiveness of child–robot interaction for reducing pain and distress during vaccination 25. A second study has shown reduction in distress, only, for 40 paediatric oncology patients requiring central venous access 26. It is timely to examine whether an interactive, humanoid robot can have an impact on children’s pain and distress associated with IVI.…”
Section: Background and Rationalementioning
confidence: 99%